Additive manufacturing of dense zirconia ceramics by fused deposition modeling via screw extrusion. Issue 1 (January 2021) - He, Qinglong; Jiang, Jie; Yang, Xianfeng; Zhang, Li; Zhou, Zhe; Zhong, Yuan; Shen, Zhijian
Highlights: A fused deposition modeling (FDM) system with screw extrusion suitable for feeding granular feedstocks with high solid loading was developed. Dense Zirconia ceramics materials and ceramics parts with complex geometries with controllable dimension accuracy was manufactured via FDM with screw extrusion. FDM system with screw extrusion was prospective for additive manufacturing of engineering ceramics such as ZrO2, Si3 N4, Al2 O3 and SiC for industrial applications. Abstract: A fused deposition modeling(FDM)system via screw extrusion suitable for feeding granular feedstocks with high solid loading was developed. Key parameters included aspect ratio of the screw, the compression ratio and pitch etc. In order to get constant extruded mass flow and wire diameter a processing window was determined by optimizing the barrel temperature, the nozzle diameter and the screwing speed. Microstructural characterization coupled with flexural strength measurement revealed that a higher printing temperature was beneficial to the inter layer bonding. The sintered zirconia ceramic samples with 99% of theoretical density of the 3 mol% yttria stabilized tetragonal zirconia polycrystal (3Y-TZP) and flexural strength of 890 ± 60 MPa was obtained. A set of zirconia ceramic parts with complex geometries and controllable dimensional accuracy was also successfully prepared for demonstrating the potential of the technique.